On a lower bound of integral solutions of the differential equations of infinite order - Korobeinik, J. F. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:О. Ф. Коробейник. Об оценке снизу для целых решений дифференциального уравнения бесконечного порядкаJ. Korobeinikas. Begalinės eilės diferencialinės lygties sveikųjų sprendinių augimas